Competing Endogenous RNA in Colorectal Cancer: An Analysis for Colon, Rectum, and Rectosigmoid Junction - Vieira, Lucas Maciel; Jorge, Natasha Andressa Nogueira; de Sousa, João Batista; Setubal, João Carlos; Stadler, Peter F.; Walter, Maria Emília Machado Telles (Frontiers in Oncology, 2021)
Background Colorectal cancer (CRC) is a heterogeneous cancer. Its treatment depends on its anatomical site and distinguishes between colon, rectum, and rectosigmoid junction cancer. This study aimed to identify diagnostic and prognostic biomarkers using networks of CRC associated transcripts that can be built based on competing endogenous RNAs (ceRNA). Methods RNA expression and clinical information data of patients with colon, rectum and rectosigmoid junction cancer were obtained from The Cancer Genome Atlas (TCGA). The RNA expression profiles were assessed through bioinformatics analysis, and a ceRNA was constructed for each CRC site. A functional enrichment analysis was performed to assess the functional roles of the ceRNA networks in the prognosis of colon, rectum and rectosigmoid junction cancer. Finally, to verify the ceRNA impact on prognosis, an overall survival analysis was performed. Results The study identified various CRC site-specific prognosis biomarkers: hsa-miR-1271-5p, NRG1, hsa-miR-130a-3p, SNHG16, and hsa-miR-495-3p in the colon; E2F8 in the rectum; DMD and hsa-miR-130b-3p in the rectosigmoid junction. We also identified different biological pathways that highlight differences in CRC behavior at different anatomical sites, thus reinforcing the importance of correctly identifying the tumor site. Conclusions Several potential prognostic markers for colon, rectum and rectosigmoid junction cancer were found. CeRNA networks could help the better understanding of the differences between and common factors in prognosis of colon, rectum and rectosigmoid junction cancer.